PENDIDIKAN ISLAM TENTANG FIGUR WANITA DALAM AL-QUR’AN: ISLAMIC EDUCATION ABOUT WOMEN FIGURE IN THE QUR'AN - Robingun Suyud El Syam; Siti Muamanah; Salis Irvan Fuadi; M. Yusuf AN; Darul Muntaha (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
The discussion about the female figure has always been an interesting issue and invites pros and cons, especially when it is related to the issue of gender equality. Through the story method, it can be concluded that the stories of women in the Qur'an emphasize an ideal concept of gender equality. The story emphasizes that an achievement in the field of spiritual and professional career does not have to be dominated by one gender only. Women have equal opportunities and abilities with men in achieving, in the political, social, economic fields to education and professional careers. By presenting and re-exploring the moral values of this inspiring woman's story, it is hoped that the women of the millennial era will be able to present a new spirit in building a nation of character.